History of the Emergence and Impact of British Imperialism in the Mughal Empire (1610–1858) - Karim, Mohamad Aqbil Wikarya Abdul; Apipudin, Apipudin; Syah, M Kautsar Thariq; Kusdiana, Ading; Hernawan, Wawan (Studi Multidisipliner: Jurnal Kajian Keislaman, 2025)
This article aims to examine the history, process, and impact of imperialism carried out by the British Government through the East India Company (EIC) on the existence of the Mughal Empire in India. This study uses a historical research methodology that includes four main stages, namely, heuristic (source collection), criticism (source verification), interpretation (source interpretation), and historiography (historical writing). The results of the study show that British imperialism had a significant impact on the sustainability of the Mughal Empire, both in terms of politics, economy, and society. Some of the important findings include the loss of the kingdom's political sovereignty, the shrinking of the territory, the weakening of military power, and the increasing economic burden on the community due to the exploitative tax system. These findings suggest that British colonialism not only changed the political structure of the Mughal Empire, but also brought about fundamental changes in the social and economic order of Indian society. Thus, this research makes an important contribution in enriching the literature on British colonialism in India by presenting an in-depth analysis of the transition of power and the legacy of imperialism.